Penatalaksanaan Holistik Pada Wanita Usia 21 Tahun dengan Asma Persisten Ringan Melalui Pendekatan Kedokteran Keluarga - Rika Partika; Azelia Nusadewiarti (Medula, 2023)
Indonesia is ranked 19th in the world regarding deaths due to asthma. Asthma is a heterogeneous disease characterized by chronic airway inflammation. Asthma is a reversible obstructive disorders which is requires control to improve the patient's quality of life. Holistic management through a family medicine approach is expected to be able to assist patients in identifying, controlling precipitating factors and preventing individuals with predisposition to asthma from developing asthma and preventing asthma patients from experiencing asthma attacks. In this study, primary data were obtained from autoanamnesis, physical examination and home visits. Secondary data was obtained from the patient's medical record. Patient Ms. C, 21 years old, has a main complaint of shortness of breath accompanied by a feeling of heaviness in the chest, coughing, and "wheezing" breath sounds that are felt to come and go and get worse, especially at night, early in the morning, cold weather, dust exposure and when the patient is under stress. The patient was diagnosed as mild persistent asthma. Internal risk factors include family history of asthma and atopy, lack of patient knowledge about the disease, and curative treatment behavior. External risk factors include lack of knowledge and attention of the family towards the patient's illness and dusty house conditions and lack of air circulation through windows. Medical and non-medical interventions are carried out for patients and families according to theory and literature with a patient-centered, family-oriented, and community-oriented approach.